The Role of the Abdullah Al Busyroni Tahfidz Al-Qur'an Islamic Boarding School in Improving the Reading Comprehension of the Qur'an - Alhafiz Ardiansyah; Muaz Tanjung (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The background to this research stems from the importance of Islamic educational institutions, particularly Islamic boarding schools (pesantren) for memorizing the Quran, as a forum for fostering community participation in reading, understanding, and practicing the teachings of the Quran. Amidst the continued lack of fluency in reading the Quran according to the rules of tajwid and makhraj, Islamic boarding schools (pesantren) offer a solution for religious education that is relevant to the community. Pesantrens focus not only on fostering resident students but also provide learning opportunities for the general public as a form of social service and Quranic outreach. This study used a qualitative method with a descriptive approach. Data were obtained through observation, interviews with Islamic boarding school administrators, ustadz/ustadzah, and the local community, and supported by documentation. The results of the study indicate that the Abdullah Al Busyroni Tahfidz Al-Qur'an Islamic Boarding School has a significant role in improving the quality of the community's Qur'an reading, through regular recitation programs, tahsin and tahfidz classes, and youth development. In addition, the Islamic boarding school also plays a role in fostering religious awareness in the community through ongoing Qur'an-based religious activities. Thus, the existence of this Islamic boarding school not only functions as a formal and non-formal educational institution, but also as a center for spiritual empowerment of the Pelintahan Village community.